Study on the effects of regional tideland's exploiting and utilization by Hangzhou Bay Bridge construction - LI Ren-an; ZHANG Min; LU Hong (浙江大学学报. 农业与生命科学版, 2003)
This paper presents the outlook of the Hangzhou Bay Bridge. According to the tideland-forming features of the Hangzhou Bay, the suggestions on exploiting and utilization of the tideland in the Hangzhou Bay were offered: When non-enclosed tideland continue fill up and can not use for aquiculture, it shall be inning within measure and provide the land for industrial use. For new innings, it should develop the industrial park, because it is high in salts and do not suitable for farmland. For old innings, it should be replant the horticultural crops and increase the economic benefits.